Ketangguhan Sosial-Ekologis Komunitas Pesisir terhadap Banjir: Studi Adaptasi dan Ketahanan di Rowoterate Kabupaten Malang - Suprianto, Agung; Yudairawan, Listyo; Ratnawati, Nurul; Ririh Windayu, Cinde; Triningsih, Luly (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2025)
This study aims to reveal the forms of socio-ecological resilience of coastal communities in Rowoterate Hamlet, which are affected by annual recurrent floods. Within the disaster geography framework, local responses are important to study as adaptive practices based on local wisdom. The study applied a qualitative case study design with thematic analysis. Data were collected through in-depth interviews with residents, community leaders, and village officials. The results show that the residents engage in both physical adaptation (e.g., elevated homes, storage platforms) and socio-cultural adaptation (e.g., mutual cooperation, ritual events, and community-based early warning systems). Although floods are recurrent, residents choose to stay due to land attachment, livelihood continuity, and strong social cohesion. This study emphasizes the importance of integrating resilience and local adaptive strategies into community-based disaster risk management. Practically, the findings of this study can serve as a reference for formulating disaster risk reduction policies that are more context-specific and sustainable in coastal areas.